Adolescence in Modern Irish History
XII, 229 p.
Keywords: This edited collection is the first to address the topic of adolescence in Irish history. It brings together established and emerging scholars to examine the experience of Irish young adults from the 'affective revolution' of the early nineteenth century to the emergence of the teenager in the 1960s.